Utilization of Whatsapp Group as a Communication Medium for Arabic Writing and Text Message Analysis - Hamidah Hamidah; Marsiah Marsiah; Rodhatul Jennah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2021)
Research on WhatsApp Group as a communication medium in the learning process and the application of foreign language communication has been widely discussed by researchers. However, research on WhatsApp Group utilization as a written communication medium to learn Arabic together is still rarely studied. Therefore, this study focuses on describing the WhatsApp Group feature used to learn Arabic together in the Arabic Education Department (Pendidikan Bahasa Arab/PBA) lecturer group and analyzing the messages contained in it. This study used a qualitative descriptive approach. This study revealed several findings: the PBA lecturer group used WhatsApp for written communication using Arabic to be a medium for continuous training. Some of the topics discussed through written communication were classified into three types: first, remarks, prayers, and invitations; second, information on important academic and non-academic matters; and third, discussion about everyday life. As for the results of the analysis of the text messages written by the PBA lecturer group, it was found that the text messages written in the WhatsApp Group in terms of choosing vocabulary and sentence structure were generally correct, and there were only a few words and sentence structures that were less precise. Theoretical implications are also described in the results of this study.